The Influence of Work Motivation and Job Training on Job Satisfaction and Employee Performance (Literature Review of Human Resource Management) - Novi Yohanes Toumahuw (Dinasti International Journal of Education Management And Social Science, 2022)
This research purpose is to build a research hypothesis that contains how the variables of job satisfaction and employee performance can increase or decrease if they are influenced by work motivation and job training. The influence between variables in this study is to build and know the research hypotheses. These hypotheses will later assist researchers in making further research on factors that can be taken into account in meeting organizational goals through increasing job satisfaction and employee performance. Human resource management is a field of science that discusses various individual, group, and organizational behaviors in relation to the development of relationships between the organizational, management, and human triangles. This scope also includes scientific articles that discuss the effect of work motivation and job training on job satisfaction and employee performance. The use of Mendeley, Google Scholar, and other online academic media is the method used by the author as part of library research. This is done by the author to observe, analyze, and evaluate in depth the influence of these variables through various appropriate and relevant literature sources. Some of the results of this Literature Review article are: 1) Work motivation influences job satisfaction; 2) Job Training affects Job Satisfaction; 3) Work motivation affects employee performance; 4) Job Training affects Employee Performance, and 5) Job Satisfaction affects Employee Performance. Several other variables can affect the increase in job satisfaction and employee performance in the organization. These variables can include Work Culture, Work Discipline, Work Environment, Leadership, and Competence.